Linguistic landscape as a mirror - Mezgec, Maja (Razprave in gradivo - Inštitut za narodnostna vprašanja (1990), 2016)
Linguistic landscape studies represent a new approach in the research on multilingualism based on the analysis of the language(s) in signs. Linguistic landscape refers to linguistic objects marking the public space. The language used in writing reflects the status and social use of languages. This paper focuses on the linguistic landscape of the area where the Slovene minority in Italy is settled. Its aim is to analyse the visibility of the Slovene language and draw a comparison between the use of the Slovene language in the linguistic landscape and the official language, i.e. Italian. The empirical research follows the methodology developed by Cenoz and Gorter (2006) with some minor adjustments. The hypothesis is that in the case studied, the status of the Slovene language is visible throughout the linguistic landscape. The discussion focuses on the importance of the visibility of minority languages and the impact of language policies on the linguistic landscape.
Keywords: Italija; Italy; slovenska manjšina; status jezika; sociolinguistics; sociolingvistika; jezikovna politika